Multidisciplinary collaboration in diagnosis and treatment of neuroleptic malignant syndrome complicated with pneumonia: report of three cases - Huachang Zhao; Sijia Lu; Xiaoyan Li; Panyun Huang; Hongming Wang; Fengmei Lu (Diagnostic Pathology, 2022)
Abstract Background Neuroleptic malignant syndrome (NMS) is a relatively rare and a potentially fatal syndrome. It is a serious complication associated with antipsychotic therapy. NMS is easily prone to pneumonia, rhabdomyolysis and other problems. However, the clinical features of NMS complicated with pneumonia remains largely unclear. Case presentation Here, we described three female adult patients of NMS complicated with pneumonia in our own hospital. The symptoms of the patients were controlled with antipsychotic drugs at admission. Symptoms such as high fever, high muscle tone, difficulty in eating, phlegm in the throat, anhelation, rhabdomyolysis and autonomic nervous dysfunction occurred 2 days after the treatment, which mainly concentrated within 1 week. In addition, they are all healed. Conclusions NMS is a rare and serious complication in psychiatric department, which is easy to be complicated with pneumonia and respiratory failure. Timely identification and early intervention could help achieve a good prognosis.